Pengaruh E-Commerce terhadap Perilaku Konsumen dalam Perspektif Ekonomi Syariah - Afdila Afdila; Ferdinan Ferdinan (STAI Auliaurrasyidin Tembilahan, 2020)
This study aimed at exploring whether e-commerce has an effect on consumer behavior in the perspective of Islamic economics in Islamic Economics students STAI Auliaurrasyidin Tembilahan. This research was motivated by the development of e-commerce as an online shopping application that has an impact on student consumer behavior. This study used a quantitative method with a simple linear regression analysis. The sample in this study was 146 respondents. In the simple linear regression test, the equation Y = 16.444 + 0.787 was obtained. Then from the t-test results obtained tcount (9.927) <ttable (1.976), so e-commerce has a significant effect on consumer behavior in the Islamic economic perspective. Based on the calculation of the coefficient of determination, the value is 0.406 or 40.6%. This data stated that the effect of e-commerce on consumer behavior in the Islamic economic perspective was 40.6%, while the remaining 59.4% was explained by other factors that were not observed in this study.